A Study in the Role of Central and Local Governments Regarding the Enforcement of Competition Law - Naoaki Okatani (Washington University Global Studies Law Review, 2002)
In the European Union, the national judicial courts of each member country and the European Court of Justice finally are determining whether an agreement constitutes an infringement of Article 81.1 of the Treaty Establishing the European Community by reviewing the regime in which the European Commission has controlled the dispensation system defined in Article 81.3. Japan developed the Decentralization Promotion Program in 1998 based on the recommendations prepared by the Decentralization Promotion Program. The Decentralization Promotion Program defines the abolition of organizationally delegated operations and the enlargement of the range of local governmental discretion. Following the Program, Japan amended the Act Against Unjustifiable Premiums and Misleading Representations in 1999 to abolish Section 9-5 in which the Japanese Fair Trade Commission (JFTC) supervised and controlled prefectural governors as well as redefine how the JFTC may provide technical advice and recommendations and request document submission and rectification. In many of the major developed countries like the United States and the Federal Republic of Germany, authority over the domain of competition law is delegated substantially to local governments, with central and local organizations responsible for the synergistic execution of the law. I will examine what form the executive authority of central and local organizations in Japan should take and how this should be coordinated synergistically. I also will discuss the relationship between the organizations in light of enhancing the executive power and effectiveness of Japan’s competition laws by increasing observation and supervisory spots supporting actions that restrain competition.
Keywords: Federalism; Germany; Antitrust law